2 2(y-2013) +(y-2010) =4035则(y-2013)(y-2010)=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 17:26:55
22(y-2013)+(y-2010)=4035则(y-2013)(y-2010)=?22(y-2013)+(y-2010)=4035则(y-2013)(y-2010)=?22(y-2013)+(y-
2 2(y-2013) +(y-2010) =4035则(y-2013)(y-2010)=?
2 2
(y-2013) +(y-2010) =4035则(y-2013)(y-2010)=?
2 2(y-2013) +(y-2010) =4035则(y-2013)(y-2010)=?
设y-2013=t,则:y-2010=t+3
(y-2013)^2+(y-2010)^2=t^2+(t+3)^2=4035,
——》2t^2+6t+9=4035,
——》t^2+3t=2013
——》(y-2013)(y-2010)=t(t+3)=t^2+3t=2013.
2 2(y-2013) +(y-2010) =4035则(y-2013)(y-2010)=?
y²+y-2
y (3y^2+8y-3)-6y(3y+2y-1)+9y
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
yy''-(y')^2=y^2y'
yy''-(y')^2=y^2y'
y+y'-2y=2x
因式分解 -y的立方-2y-y
微分方程y - 2y' + y = x
2y''+y'-y=0
因式分解 (y^2+y)^2-8(y^2+y)+12
(y平方+2y)(y平方+2y+2)+1
[(x-y)^2-(x+2y)(x-2y)]/y
y'(2y-y')=y^2*(sinx)^2求解,
y^2+y-2/y^2+4y+4约分
(y^2)^4y-(-2y)^3y^6=
(3y+2)(y-4)-3(y-2)(y-3)
化简y(x+y)+(x+y)(x-y)-x^2